2011
DOI: 10.1016/j.jcm.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

High hamstring tendinopathy in 3 female long distance runners

Abstract: Objective: The purpose of this case report is to describe and discuss the clinical presentation, diagnosis, and management of 3 female long distance runners with high hamstring tendinopathy. Clinical Features: Three female runners presented to a chiropractic office with proximal hamstring pain that was aggravated by running. Increasing mileage, hills, and/or interval training preceded the onset of symptoms in each case. The subjects all displayed weakness of the hip abductors, pelvic joint dysfunction, hamstri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
(32 reference statements)
0
22
0
1
Order By: Relevance
“…Extrinsic factors include training errors, such as increasing volume or intensity too quickly, particularly the sudden introduction of sprinting, lunging, hurdles, or hills. Several case series 42,95 have been identified that report these training errors to precede PHT. These activities require the hamstring to contract or lengthen while in hip flexion and may result in provocative tensile and compressive load at the tendon insertion.…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…Extrinsic factors include training errors, such as increasing volume or intensity too quickly, particularly the sudden introduction of sprinting, lunging, hurdles, or hills. Several case series 42,95 have been identified that report these training errors to precede PHT. These activities require the hamstring to contract or lengthen while in hip flexion and may result in provocative tensile and compressive load at the tendon insertion.…”
Section: Anatomymentioning
confidence: 99%
“…Handheld or fixed dy namometry may be used to assess ham string strength. 43,90,95,96 In the absence of these instruments, the authors suggest testing strength in a legcurl machine to preferentially isolate the hamstring mus cles, as a loaded hamstring curl achieves high levels of biceps femoris and semi tendinosus activity with minimal gluteus maximus (GMax) recruitment. 4 Other kineticchain deficits have the potential to increase hamstring origin stress concentration.…”
Section: Symptom Management: Load Modificationmentioning
confidence: 99%
“…On clinical examination, there is often palpable tenderness and pain over the ischial tuberosity against resisted knee flexion. Furthermore, active stretching of the hamstrings recreates the pain at the site of the ischial © C I C E d i z i o n i I n t e r n a z i o n a l i plasma (PRP) injection 19,[23][24][25]38,39 . When compared to a combined NSAID, physiotherapy and a hamstring specific exercise program, SWT had significantly better results with a mean follow-up of 10.7 months 19 .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…3,4 Several nonsurgical options have been described for the treatment of PHT, including shockwave therapy, 7 eccentric exercises with trunk/pelvis musculature strengthening, 10,11 corticosteroid injection, 33 massage/soft tissue mobilization, 10,17 platelet-rich plasma injection, 31 and a combined chiropractic approach. 32 A recent description of 2 runners with PHT reported positive results with conservative treatment consisting of eccentric strengthening, lumbopelvic stabilization exercises, and trigger point dry needling of the hamstring and adductor magnus muscles. 11 …”
mentioning
confidence: 99%